Self-congruity Theory in Red Tourism: A Study of Shaoshan City, China. Issue 1 (2nd January 2022) - Zhou, Meijing; Yan, Le; Wang, Fuyuan; Lin, Mingshui
ABSTRACT: As a heritage tourism and patriotism education in China, red tourism has strong value-expressive attributes, which makes it of great significance to examine self-congruity (SC) theory in a red destination. This study explores and compares the effects of SC and functional congruity (FC) on tourist satisfaction (TS) and destination loyalty (DL) by using structural equation modeling based on a sample of 332 tourists in Shaoshan city, a popular red destination in China. The findings indicate that SC of red tourists explains much higher variation of FC than that of other tourists. In addition, SC exerts equal effects on TS as FC and shows greater influence on DL than FC. This study sheds new lights on understanding the role of SC in destination marketing research and practices.